To Know is to See: the Contribution of the Odeporic Narration in the Voyage pittoresque of Abbot Saint-Non - Ottavio Amaro (ArcHistoR Architettura Storia Restauro: Architecture History Restoration, 2019)
The rediscovered interest in southern Italy characterizing the 18th and 19th centuries coincided with an Arcadian vision of the places there with their strong identity, deeply rooted into history. That vision thus also involved Calabria to be replaced later by a negative rationale generating short-sighted policies and improper planning. We can say that the region, losing its self-awareness and consequently its figurative self-consciousness, has passively endured misrepresentation. The new iconography of Calabria, in fact, has increasingly tended to be iconoclastic within a local scenario of acritical resignation to degradation and lack of self-perception. The current project design aimed at the regeneration of the Calabrian landscape can start from the actual knowledge and awareness of the region’s figurative heritage. The thirty-five images of Calabria created by Désprez and Châtelet for the Voyage pittoresque, provide fundamental iconographic and iconological documentary evidence. They are parts of one single project aimed, perhaps as a first example in history, at the official composite representation of Calabria. As in Gombrich’s words «That a picture looks like nature often means only that it looks the way nature is usually painted»; the images reported by Saint-Non bring to light Calabria’s existence; they show the region to Europe highlighting its pastoral and Arcadian simplicity, archeological remains, a system of settlements either clinging to steep hill sides or nested on secluded plains. This imagery can be compared with the most up-to-date representation tools for landscaping.